THE ASSESSMENT OF STUDENTS’ ENGLISH SPEAKING ABILITY - Mukammal (al-Hikmah : Jurnal Studi Islam, 2021)
Abstract: This Study is intended to assess students’ English speaking ability in Syaikh Zainuddin NW Anjani Senior High School East Lombok which includes; the categories of students’ English speaking ability, the problems are experienced by students when they speak English and factors affect students’ English speaking ability. The data was collected through audio and video recording of students’ group discussions and dept interviews with the head master, English teachers, language advisors and students. The data was analyzed using descriptive qualitative and quantitative method. The results of this study are; first, the categories of students’ English speaking ability are 86.8 % students in high, 11.2 % student medium and 2.8 % in low category. Second, the problems are experienced by students when they speak English are; difficult to begin, vocabularies mastering, pronunciation, and grammatically, and third, factors affect students’ English speaking ability are; environment, learning method, control, language rules, rewards and punishments.